Hemodynamic and Rhythmologic Effects of Push-Dose Landiolol in Critical Care-A Retrospective Cross-Sectional Study - Sebastian Schnaubelt; Felix Eibensteiner; Julia Oppenauer; Daniel Tihanyi; Marco Neymayer; Roman Brock; Andrea Kornfehl; Christoph Veigl; Valentin Al Jalali; Sonja Anders; Barbara Steinlechner; Hans Domanovits; et al. (MDPI AG, 2023)
Background: The highly β1-selective beta-blocker Landiolol is known to facilitate efficient and safe rate control in non-compensatory tachycardia or dysrhythmia when administered continuously. However, efficacy and safety data of the also-available bolus formulation in critically ill patients are scarce. Methods: We conducted a retrospective cross-sectional study on a real-life cohort of critical care patients, who had been treated with push-dose Landiolol due to sudden-onset non-compensatory supraventricular tachycardia. Continuous hemodynamic data had been acquired via invasive blood pressure monitoring. Results: Thirty patients and 49 bolus applications were analyzed. Successful heart rate control was accomplished in 20 (41%) cases, rhythm control was achieved in 13 (27%) episodes, and 16 (33%) applications showed no effect. Overall, the heart rate was significantly lower (145 (130-150) vs. 105 (100-125) bpm, p < 0.001) in a 90 min post-application observational period in all subgroups. The median changes in blood pressure after the bolus application did not reach clinical significance. Compared with the ventilation settings before the bolus application, the respiratory settings including the required FiO2 after the bolus application did not differ significantly. No serious adverse events were seen. Conclusions: Push-dose Landiolol was safe and effective in critically ill ICU patients. No clinically relevant impact on blood pressure was noted.